Reported maladaptive decision-making in unipolar and bipolar depression and its change with treatment. (November 2017) - Alexander, Lara F.; Oliver, Alison; Burdine, Lauren K.; Tang, Yilang; Dunlop, Boadie W.
Abstract: Mood disorder patients frequently experience difficulty making decisions and may make sub-optimal decisions with adverse life consequences. However, patients' styles for decision-making when ill and after treatment have received little study to date. We assessed healthy controls (HC, n = 69) and patients with major depressive disorder (MDD, n = 61) or bipolar disorder (BP, n = 26) in a current major depressive episode using the Melbourne Decision-making Questionnaire. A subset of participants was re-evaluated after completing six weeks of pharmacotherapy. HC demonstrated significantly greater use of the healthy vigilance style, and significantly lower use of maladaptive decision-making styles, than the MDD and depressed BP patients. After six weeks of treatment, neither the MDD nor BP patients reported meaningful improvements in the vigilance style of decision-making, but scores on most maladaptive decision-making styles declined. BP patients who remitted reported significantly lower buckpassing and procrastination scores than healthy controls. Among MDD patients, however, the maladaptive passive buckpassing style of decision-making did not significantly diminish. For MDD patients, reported decision-making styles may remain impaired even after achieving remission. Among BP patients, low levels of adaptive vigilance decision-making may be a trait component of the illness, whereas for MDD patients, reported maladaptive passive decision-making styles are persistent. Highlights: Actively depressed mood disorder patients have maladaptive decision-making styles. Pharmacotherapy did not improve the use of adaptive decision-making. A passive decision-making style may be a trait characteristic in major depression.